STRATEGI AFRIKA SELATAN MENGEMBALIKAN CITRA DAN MEMPERSATUKAN BANGSA MELALUI PIALA DUNIA FIFA 2010 - Saudi, Ahmad; Yelta, Den (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This paper describes how South Africa use World Cup FIFA 2010 as diplomacystrategy to returns the image and uniting the nations. South Africa which known withApartheid and its made nation’s image become worse in the world. Criminality issues,ethnical conflicts, HIV/AIDS are main factors. South Africa had choosen as host of firstWorld Cup in the African continent, make this country have an expectations to takeadvantage from this momentum to change world image about South Africa more better.Authors collected data of books, journals, media, websites in search for the source ofthis research. This study uses the Kontruktivis paradigm. The theory used is PublicDiplomacy and concept of Sports Diplomacy. Theoretical framework on this research isguided by qualitative explanation methods. Writing technique in this research is through bylibrary research.This study shows how South Africa can take advantage of the 2010 FIFA World Cupas srtategy diplomacy in achieving the national interest is to restore the image and integrityof the nation. Not only required a consistent state policy but also after the 2010 FIFA WorldCup is maintained image and integrity nation South Africa better.Keywords: South Africa, Diplomacy, Apartheid, World Cup FIFA 2010.